Understanding digital ethics : cases and contexts - Beever, Jonathan, 1980-; McDaniel, Rudy; Stanlick, Nancy A. (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Rapid changes in technology and the growing use of electronic media signals a need for understanding both clear and subtle ethical and social implications of the digital, and of specific digital technologies. Understanding Digital Ethics: Cases and Contexts is the first book to offer a philosophically grounded examination of digital ethics and its moral implications. Divided into three clear parts, the authors discuss and explain the following key topics : Becoming Literate in Digital Ethics Moral Viewpoints in Digital Contexts Motivating Action in Digital Ethics Speed and Scope of Digital Information Moral Algorithms and Ethical Machines The Digital and the Human Digital Relations and Empathy Machines Agents, Autonomy, and Action Digital and Ethical Activism. The book includes cases and examples that explore the ethical implications of digital hardware and software including videogames, social media platforms, autonomous vehicles, robots, voice enabled personal assistants, smartphones, artificially intelligent chatbots, military drones, and more. Understanding Digital Ethics is essential reading for students and scholars of philosophical ethics, those working on topics related to digital technology and digital/moral literacy, and practitioners in related fields"--
Cultural Change and Relationships -- Special Considerations -- Next Up -- References -- Part 3 Implications of Digital Ethics -- Chapter 7 Digital Relations and Empathy Machines -- Defining Key Terms: Empathy, Sympathy, and Other Strange Beasts -- So What for Digital Ethics? -- Digital Desensitization -- Nonhuman Empathy -- Empathy Machines -- Next Up -- References -- Chapter 8 Agency, Autonomy, and Action -- Autonomy and the Autonomous -- From Apple Inc. to Teenage Repellant: Agency in the Digital Age -- Virtual Good and Evil in Networked Spaces: Digital Agency and Sociality -- The Physical Rise and Virtual Fall of Justine Sacco: Digital Agency and Time -- Ghosts in the Machine: Self-Contained Electronic Memorials -- Next Up -- References -- Chapter 9 Digital and Ethical Activism -- Challenges of Motivating Action through Policy -- Policymaking in Research and Professional Organizations -- Policymaking for Individuals and Communities -- Policies for the Digital -- Motivating Action through Practice -- Political Action -- Administrative Action -- Personal and Community Action -- Water Warriors: The Concerned Citizens of Brant -- Next Up -- References -- Conclusion: Digital and Moral Literacies -- Living in (Digital) Communities -- Case Studies and Argumentation -- Future Work -- Understanding Digital Ethics -- References -- Appendix: Developing Cases in Digital Ethics -- Index.
Includes bibliographical references and index.
Jonathan Beever is Assistant Professor of Ethics and Digital Culture with the Department of Philosophy and the Ph.D. Program in Texts and Technology at the University of Central Florida, USA. He is co-editor (with N. Morar) of Bioethics, Science, and Public Policy and (with V. Cisney) of The Way of Nature and the Way of Grace: Philosophical Footholds on Terrence Malick's The Tree of Life. Rudy McDaniel is Professor of Games and Interactive Media in the Nicholson School of Communication and Media and Director of the School of Visual Arts and Design at the University of Central Florida, USA. He is co-author (with J.D. Applen) of The Rhetorical Nature of XML and (with Joseph Fanfarelli) Designing Effective Digital Badges: Applications for Learning, both published by Routledge. Nancy A. Stanlick is Professor of Philosophy and Associate Dean in the College of Arts and Humanities at the University of Central Florida, USA. She has published five books: Philosophy in America: Volumes I and II (co-authored and co-edited with Bruce Silver), Asking Good Questions: Case Studies in Ethics and Critical Thinking (with Michael Strawser), The Essential Leviathan: A Modernized Edition, and American Philosophy: The Basics (also available from Routledge).
Description based on online resource; title from digital title page (viewed on January 22, 2020).
eBooks on EBSCOhost
Keywords: Technology -- Moral and ethical aspects; Digital media -- Moral and ethical aspects; Technologie -- Aspect moral; Médias numériques -- Aspect moral; PHILOSOPHY / General; Digital media -- Moral and ethical aspects; Technology -- Moral and ethical aspects